Integrated Fire Safety Model for Ship Engine Rooms - Sarifuddin; Musriady; Adnan; Hasan; Muh. Arifin (International Journal of Marine Engineering Innovation and Research, 2026)
Engine room fire remains one of the most critical threats to ship safety because it involves the interaction of fuel systems, lubrication systems, hot surfaces, electrical installations, confined-space operations, and emergency response constraints. Although international regulations such as SOLAS, STCW, and IMO Model Courses have established a comprehensive normative framework, fire incidents in ship engine rooms continue to occur. This condition indicates a persistent gap between regulatory standards, technological capability, and operational implementation onboard. Previous studies have examined engine room fire from different perspectives, including technical failure, fire detection, suppression systems, human factors, and safety barriers. However, most of these studies remain fragmented and do not sufficiently explain how technical readiness, managerial implementation, and human capability interact in real ship operations. This article aims to develop an integrated fire safety model for ship engine rooms by synthesizing those three dimensions into one analytical framework. The study applies an integrative literature review and conceptual model development approach based on maritime safety regulations, peer-reviewed maritime fire studies, and organizational safety theory. The results show that effective fire prevention and response depend on the simultaneous strength of technical systems, procedural discipline, and crew capability. The proposed model offers practical implications for shipping companies, maritime education institutions, and safety regulators in strengthening evidence-based fire safety in commercial vessels.